Daily two-photon neuronal population imaging with targeted single-cell electrophysiology and subcellular imaging in auditory cortex of behaving mice - Huang, Junjie; Liang, Susu; Li, Longhui; Li, Xingyi; Liao, Xiang; Hu, Qianshuo; Zhang, Chunqing; Jia, Hongbo; Chen, Xiaowei; Wang, Meng; Li, Ruijie (Frontiers in Cellular Neuroscience, 2023)
Quantitative and mechanistic understanding of learning and long-term memory at the level of single neurons in living brains require highly demanding techniques. A specific need is to precisely label one cell whose firing output property is pinpointed amidst a functionally characterized large population of neurons through the learning process and then investigate the distribution and properties of dendritic inputs. Here, we disseminate an integrated method of daily two-photon neuronal population Ca2+ imaging through an auditory associative learning course, followed by targeted single-cell loose-patch recording and electroporation of plasmid for enhanced chronic Ca2+ imaging of dendritic spines in the targeted cell. Our method provides a unique solution to the demand, opening a solid path towards the hard-cores of how learning and long-term memory are physiologically carried out at the level of single neurons and synapses.